Comparison of urine protein creatinine ratio and 24 hours urine protein in detecting preeclampsia (Nepal Journal of Obstetrics and Gynaecology, 2019)
Aim: To assess the diagnostic accuracy of spot urine protein-creatinine ratio for detection of proteinuria in Preeclampsia.Methods: Cross Sectional Descriptive Study was conducted in a total of 38 pregnant women in Paropakar Maternity and Women’s Hospital in study period of 3 month. The correlation between protein- creatinine ratio in spot urine samples and urinary protein excretion in 24-hour collections were analyzed. Results: Comparison of 24 hours urinary protein and protein- creatinine ratio in women with preeclampsia shows a significant correlation (r=0.911, p300mg, >2000mg and >3000mg/day were 0.946 (95%CI 0.873-1.019), 1 (95% CI 1.00-1.00) and 0.957 (95%CI 0.897- 1.016) respectively.Conclusions: Spot urine protein-creatinine ratio is as accurate as to 24 hours urine protein determination of proteinuria in Preeclampsia.